2014
DOI: 10.1063/1.4886183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of point and grain boundary defects on the mechanical behavior of monolayer MoS2 under tension via atomistic simulations

Abstract: Negative differential resistance and effect of defects and deformations in MoS2 armchair nanoribbon metaloxide-semiconductor field effect transistor Atomistic simulation is used to study the structure and energy of defects in monolayer MoS 2 and the role of defects on the mechanical properties of monolayer MoS 2 . First, energy minimization is used to study the structure and energy of monosulfur vacancies positioned within the bottom S layer of the MoS 2 lattice, and 60 symmetric tilt grain boundaries along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…However, as a material for real applications, a comprehensive understanding of mechanical properties plays a crucial role [12][13][14]. Mechanical properties of semiconducting MoS 2 films have been studied both experimentally [15,16] and theoretically [17][18][19][20][21][22][23]. Nevertheless, to the best of our knowledge, mechanical responses of all-MoS 2 heterostructures have been studied neither theoretically nor experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…However, as a material for real applications, a comprehensive understanding of mechanical properties plays a crucial role [12][13][14]. Mechanical properties of semiconducting MoS 2 films have been studied both experimentally [15,16] and theoretically [17][18][19][20][21][22][23]. Nevertheless, to the best of our knowledge, mechanical responses of all-MoS 2 heterostructures have been studied neither theoretically nor experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Former studies suggested that the grain boundaries of the 2H monolayer MoS 2 have important effects on the electronic, magnetic and transport properties. [24][25][26][27] Similar with that of grain boundaries, the 1T/2H phase interface are supposed to be connected with many physical properties. Moreover, in order to reliably design future low-dimensional devices based on the 1T/2H MoS 2 heterostructures, many issues should be clarified before realize its full applications.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In addition to the native defects unintentionally introduced during growth, defects may also be produced deliberately at the postgrowth stage. [15][16][17] There are various types of structural defects in MoS 2 , such as point defects, 13 dislocations, 18 grain boundary, 19 or topological. 20 The point defect is one of the native defects which have been studied both in experiment 13 and theory.…”
Section: Introductionmentioning
confidence: 99%